The great business challenge: strategic management and value creation for customers - Mendoza Mendives, Juan Carlos (2022)
Strategic management and the creation of value for customers are part of any company that seeks to stay in the market, which is why both are the pillars of this great business challenge. This research is based on the restaurant sector, whose main objective was to determine the relationship between strategic management and the creation of value for the customers of the Toque Marino SAC restaurant. All the analysis was carried out based on a quantitative approach, applying the data collection instrument of the Likert type questionnaire to 270 clients, who gave their perception regarding the strategic management that the company has and the creation of value for the clients it performs. . The results allowed to affirm that there is a direct and significant relationship between strategic management and the creation of value for the clients of the restaurant under study, since a Spearman correlation coefficient Rho = 0.793 was obtained; concluding that both strategic management and value creation are one of the great challenges that companies face today, especially restaurants that seek not only to provide quality service but also to satisfy needs, desires and even aspirations of your customers. In this sense, the Toque Marino SAC restaurant, which is the company for this research, should improve the regular result obtained in this study by, for example, creating a marketing area and customizing the service.